Are we leaving them behind? a rhetorical analysis of <veteran> on the No One Left Behind website - Wilson, Delta Dawn (Kansas State University, 2019)
Ideographs are words or phrases which represent a common belief held within a culture (Cloud, 2004). These words and phrases invoke feelings and attitudes an audience has been conditioned to accept, and in strong cases, act upon (Cloud, 2004; McGee, 1980). One such term is , which in a U.S. context invokes feelings of honor and respect, and attitudes which put those who fit in the category on a pedestal above citizens. This analysis seeks to understand the importance of defining who deserves the title of by examining the use of the term by a nonprofit organization, No One Left Behind, to describe their clients as . No One Left Behind (NOLB) serves individuals who have received Special Immigrant Visas (SIVs) as a result of their service to the U.S. military. SIV recipients are citizens of Iraq and Afghanistan who served as interpreters and cultural ambassadors to the U.S. military, and as a result are persecuted by the Taliban and Al Qaeda. Because of this persecution, they immigrate to the U.S. NOLB makes the argument that these individuals should be included in the ideograph because of their service to the U.S. military, regardless of their citizenship status. Therefore, this analysis examines the consequences of attempting to include such a marginalized group in the ideograph.
Keywords: Veteran, rhetoric, refugee